Understanding human papillomavirus vaccine response and efficacy in people living with HIV: A systematic mixed studies review and meta-analysis. - Alvine M Akumbom; Alanna J Bergman; Howard Strickler; Chakra Budhathoki; Manka Nkimbeng; Raeven Grant; Nancy R Reynolds; Kawsar R Talaat (PLOS Global Public Health)
Coinfection with human papillomavirus (HPV) and HIV compounds the risks of developing cervical, anal, and HPV-associated oral neoplasia. Safe prophylactic vaccines are available to prevent HPV infections in people with HIV(PWH). Yet, vaccine efficacy and duration of protection remain questionable. Historically, the efficacy of vaccines has been suboptimal in PWH compared to people without HIV (PWoH).A systematic review of HPV vaccine trials in PWH was conducted using PRISMA guidelines. Outcomes of interest were vaccine efficacy, immunogenicity, and predictors of HPV vaccine efficacy. A secondary outcome was to assess age and sex differences. Efficacy was reviewed as cervical/anal/oral lesions or neoplasia, and incident or persistent HPV infection following vaccination. A random effects meta-analysis was performed comparing geometric mean titer (GMT) in PWH to PWoH. Twenty-eight studies out of 988 were eligible for inclusion in our study, and qualitatively synthesized. Eight of these studies were meta-analyzed. GMT results of HPV16 and HPV18 genotypes were significantly lower in PWH; Hedges's g -0.434 (95% CI: -0.823, -0.046) and Hedges's g -0.57 (95% CI: -0.72, -0.43), respectively. The mean difference in GMT for HPV18 between PWH and PWoH was -536.23 (95% CI: -830.66, -241.81); approximately 22 times higher than HPV18 seropositivity cut-offs, assuming milli-Merck Units per milliliter. Risk factors for incident or persistent infections in PWH included: failure to seroconvert after vaccination, baseline CD4+ T-cell count <500 cells/mm3, early age of sexual debut, HIV viral load ≥ 400 copies/mL. There was a trend towards decreased HPV vaccine efficacy in studies that included enrollees with a history of AIDS or AIDS-defining illness.Applying existing evidence of HPV vaccine efficacy on meaningful clinical outcomes in PWH is questionable. This could be influenced by the diversity of eligibility criteria across clinical trials of HPV vaccine efficacy. Precision medicine may offer novel alternatives for evaluating HPV vaccine efficacy in PWH.